Product Innovation on Customer Satisfaction and Brand Loyalty of Smartphone Users - Sumitro Sarkum; Abd. Halim; Yuni Winarti (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
This study investigates the effect of product innovation attributes (Relative advantage, Complexity, Compatibility, Trialability, and observability) on customer satisfaction and loyalty with experience as a moderator between customer satisfaction and brand loyalty. This study uses quantitative methods, using the help of SPSS 23, and uses a path analysis approach to determine the relationship between variables. Based on a sample of 100 people living in the Labuhan Batu Regency area, it was found that Relative advantage, Complexity, Compatibility, Trialability, and Observability had a positive effect on customer satisfaction. These results also found that the product innovation attribute was a major predictor of customer satisfaction. The results of the study reveal that loyal customers use smartphone services in accordance with and consistent with the given perceptions. In addition, the research results illustrate that customer satisfaction has a significant effect on brand loyalty. Furthermore, this study also found that experience significantly moderates customer satisfaction and brand loyalty. As a practical implication in good market competition, companies need to understand the needs of customers and provide added value to customers by providing innovative products. Innovation in a product can increase customer satisfaction and make customers commit to a brand. managers need to understand customer needs by creating value accordingly. This study is the first to investigate the relationship between product innovation attributes, customer satisfaction and experience as a moderator. Future research is expected to analyze the role of experience as an independent variable in influencing customer satisfaction and brand loyalty.